Roll core and battery

By bonding the separator to the electrode sheet and setting a convex portion in the composite part, the problem of cracks and powder loss in the core-rolled electrode sheet and the separator are easily generated during charging and discharging, and the safety and life of the battery are improved.

CN119481341APending Publication Date: 2025-02-18ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411763738.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The pole sheet of the roll core is subjected to uneven force at the arc area, causing cracks and active substances to lose powder, and the diaphragm is prone to stretch and thin during charging and discharging, increasing the risk of short circuit.

Method used

Design a core to form a composite part by bonding the diaphragm to the first electrode sheet and setting a plurality of convex parts on the composite part to increase the electrolyte storage space, improve the elastic deformation ability of the electrode sheet and the diaphragm, and dispersed expansion. to avoid stress concentration.

Benefits of technology

Effectively inhibit the inversion of the electrode sheet, reduce the shrinkage of the diaphragm, reduce the risk of short circuit, improve the electrolyte infiltration ability, alleviate the stress in the core, and prevent cracks and powder loss problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481341A_ABST
    Figure CN119481341A_ABST
Patent Text Reader

Abstract

The invention provides a roll core and a battery, and relates to the technical field of energy storage. The roll core provided by the invention comprises a first pole piece, a diaphragm and a second pole piece, the first pole piece, the diaphragm and the second pole piece are laminated and wound to form a winding core; the diaphragm comprises a first diaphragm layer and a second diaphragm layer; the first diaphragm layer comprises a first part exceeding the first pole piece, the second diaphragm layer comprises a second part exceeding the first pole piece, and the first part and the second part are adhered; the first diaphragm layer, the first pole piece and the second diaphragm layer form a composite part; the composite part comprises a first surface close to the center of the roll core and a second surface deviating from the center of the roll core; a plurality of convex parts are arranged on the composite part, and the convex parts are bent and protrude from the first surface to the second surface. The roll core provided by the invention has excellent obdurability, and can improve the problems of cracks and powder falling of the pole piece and easy stress thinning of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to a winding core and a battery. Background Art

[0002] Battery cell safety is the most critical part of battery technology, which is directly related to the performance of the equipment and the safety of the users. In addition to optimizing and innovating battery materials to improve battery safety, designing and improving the battery cell structure is also effective.

[0003] At present, the inner and outer sides of the pole piece of the winding core are subjected to different forces in the arc area. The outer side is mainly subjected to tensile force, and the inner side is mainly subjected to compressive force. Especially for the inner layer part with a smaller curvature radius of the winding core, it is easy to cause cracks and active materials to fall off and powder. Summary of the invention

[0004] The present application provides a winding core and a battery, which can improve the problems of cracks and powder loss of pole pieces.

[0005] In order to achieve the above objectives, this application provides the following technical solutions:

[0006] A first aspect of the present application provides a winding core, including a first pole piece, a diaphragm, and a second pole piece;

[0007] The first pole piece, the diaphragm and the second pole piece are stacked and wound to form the winding core; the diaphragm includes a first diaphragm layer and a second diaphragm layer; the first diaphragm layer is located between the first pole piece and the second pole piece; the first pole piece is located between the first diaphragm layer and the second diaphragm layer;

[0008] The first diaphragm layer includes a first portion extending beyond the first pole piece, the second diaphragm layer includes a second portion extending beyond the first pole piece, and the first portion and the second portion are adhered;

[0009] The first diaphragm layer, the first pole piece and the second diaphragm layer form a composite part; the composite part includes a first surface close to the center of the winding core and a second surface away from the center of the winding core;

[0010] The composite part is provided with a plurality of convex parts, and the convex parts are bent from the first surface toward the second surface to protrude the composite part.

[0011] In a possible implementation manner, the composite portion further includes a concave portion arranged corresponding to the plurality of convex portions.

[0012] In a possible implementation, the first pole piece includes a straight section and an arc section, and the convex portion is arranged on the straight section and / or the arc section.

[0013] In a possible implementation manner, a protruding height of the protruding portion of the straight segment is greater than a protruding height of the protruding portion of the arc segment.

[0014] In a possible implementation, the straight section of the first pole piece is bonded to the first diaphragm layer and the second diaphragm layer respectively;

[0015] The arc segment of the first pole piece is not bonded to the first diaphragm layer or the second diaphragm layer.

[0016] In a possible implementation manner, the convex portion includes a first convex portion located on the first diaphragm layer, a second convex portion located on the first pole piece, and a third convex portion located on the second diaphragm layer.

[0017] In a possible implementation, a vertical distance between the vertex of the second convex portion and the first surface is 3-50 micrometers;

[0018] and / or, the curvature radius R1 of the second convex portion is 0.5 mm ≤ R1 ≤ 8 mm;

[0019] And / or, a distance L1 between adjacent second protrusions is 3 mm ≤ L1 ≤ 10 mm.

[0020] In a possible implementation, the composite portion is spaced apart along its length direction to form at least two spaced-apart raised areas; the raised area includes a plurality of the convex portions.

[0021] In one possible implementation, the composite part also includes a lug area located between the two raised areas, and along the length direction of the first pole piece, the distance from the edge of the lug area to the adjacent raised area is 1.5-20 mm; and / or, along the width direction of the first pole piece, the distance from the raised area to the adjacent edge of the composite part is 0.5-20 mm; and / or along the length direction of the first pole piece, the distance from the raised area to the adjacent edge of the composite part is 3-50 mm.

[0022] In a possible implementation, a ratio of a vertical distance between the second protrusion of the first pole piece and the first surface to a thickness of the first pole piece is in a range of 10% to 60%.

[0023] In a possible implementation, along the thickness direction of the composite portion, a ratio of a distance between the centers of two adjacent second protrusions to a diameter of the second protrusion is in a range of 1.05-3.

[0024] In a possible implementation, the tensile strength of the diaphragm is greater than or equal to 2500 kgf / cm 2 ; and / or, the puncture strength of the diaphragm is greater than or equal to 260gf.

[0025] In a possible implementation, the first electrode sheet is a positive electrode sheet, the positive electrode sheet includes a positive electrode collector, and the tensile strength of the positive electrode collector is greater than or equal to 200 MPa; or, the first electrode sheet is a negative electrode sheet, the negative electrode sheet includes a negative electrode collector, and the tensile strength of the negative electrode collector is greater than or equal to 550 MPa.

[0026] In a possible implementation, the first electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer. In a nitrogen environment, the weight loss rate of the positive electrode active material layer from 35° to a temperature range of 300°C to 600°C is ρ, and ρ satisfies: 1.1% to 6%.

[0027] In a possible implementation, the positive electrode active material layer includes a positive electrode active material and a binder, and the binder accounts for 0.5%-2% by mass of the positive electrode active material layer.

[0028] In one possible implementation, the first electrode sheet is a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer includes a silicon-carbon composite material and / or a silicon-oxygen composite material, and the percentage of silicon element in the negative electrode active layer is 5%-50%; and / or the particle size Dv50 of the silicon-carbon composite material or the silicon-oxygen composite material is 6μm-15μm.

[0029] In a possible implementation, the absolute plastic deformation rate of the diaphragm is ε1=50%-1600%; and / or the relative plastic deformation rate of the diaphragm is ε2=70%-90%.

[0030] A second aspect of the present application provides a battery, comprising a roll core provided by any of the above technical solutions and a packaging film covering the roll core.

[0031] In a possible implementation manner, a recessed portion is provided on the packaging film, the recessed portion is recessed toward a side away from the winding core body, and the recessed depth of the recessed portion is 10-35 μm.

[0032] In a possible implementation, the packaging film includes a PP layer, an aluminum foil layer, and a nylon layer that are stacked, the PP layer is located on a side of the aluminum foil layer close to the winding core, and the PP layer is provided with the recessed portion.

[0033] In a possible implementation, the ratio of the depression depth of the depression to the thickness of the aluminum foil layer is less than or equal to 40%; and / or the projection of the depression is circular, and the diameter of the circular embossed portion is 0.8-2 mm.

[0034] In a possible implementation, within a unit area, the ratio of the number of the recessed portions to the area of ​​the side surface of the packaging film is 0.25-0.5:1.

[0035] The winding core provided in the first aspect of the present application has at least the following beneficial effects:

[0036] The winding core of the present application bonds the first part and the second part of the diaphragm, so that the first diaphragm layer and the second diaphragm layer are respectively bonded to the first pole piece to form a composite part, thereby inhibiting the pole piece from turning inward, while reducing the shrinkage of the diaphragm at high temperature, and reducing the risk of short circuit caused by contact between the positive and negative pole pieces;

[0037] In addition, a plurality of convex portions are provided on the composite portion, and the convex portions are bent and protrude from the composite portion from the first surface toward the second surface. The composite portion forms a space for accommodating electrolyte between the convex portions of the composite portion and the second pole piece, thereby increasing the storage space for the electrolyte, improving the infiltration capacity of the electrolyte in the area, and avoiding abnormal situations such as insufficient electrolyte and poor infiltration between pole piece layers;

[0038] Furthermore, the overall shape of the composite part is uneven, which improves the elastic deformation capacity of the pole piece and diaphragm of the winding core and increases the deformation space of the pole piece and diaphragm. When the battery expands during a cycle, the internal stress and expansion force of the winding core can be relieved, and the expansion force on the pole piece or diaphragm can be dispersed, thereby avoiding stress concentration on the pole piece or diaphragm, thereby eliminating the problem of tensile deformation and thinning of the diaphragm or cracks on the pole piece or powder loss of the active material layer. Moreover, the composite part belongs to the same whole. During the battery cycle expansion process, since convex portions are formed on both the diaphragm and the pole piece, and the first pole piece and the diaphragm are bonded together, the first pole piece and the diaphragm can extend at the same frequency under the premise of effectively dispersing the internal stress and expansion force, thereby preventing frictional powder loss caused by the mismatch in the extension of the pole piece and the diaphragm.

[0039] The battery provided in the second aspect of the present application has all the beneficial effects of the winding core provided in the first aspect of the present application, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 A schematic diagram showing a first pole piece or a second pole piece in a winding core provided in an embodiment of the present application after being bonded to and wound with a diaphragm;

[0042] Figure 2 A schematic diagram of the unfolding of the composite part of the winding core provided in an embodiment of the present application;

[0043] Figure 3 A schematic diagram of the embossing on the inner side of the film shell after punching the packaging film of the roll core provided in an embodiment of the present application;

[0044] Figure 4 A schematic diagram of a method for testing the plastic deformation rate and tensile strength of a membrane of a winding core provided in an embodiment of the present application;

[0045] Figure 5 A schematic diagram of the battery puncture process provided in an embodiment of the present application.

[0046] Description of reference numerals:

[0047] 100, composite part; 110, first pole piece; 120, diaphragm; 130, second pole piece; 140, raised area; 141, convex part; 150, pole ear area; 200, packaging film.

[0048] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0049] As mentioned in the background technology, cell safety is the most critical part of battery technology, directly related to the performance of the equipment and the safety of the user. In addition to optimizing and innovating the battery material to improve battery safety, it is also effective to design and improve the cell structure. At present, the inner and outer sides of the pole piece of the winding core are subjected to different forces in the arc area. The outer side is mainly subjected to tensile force, and the inner side is mainly subjected to compressive force. Especially for the inner layer of the winding core with a smaller curvature radius, it is easy to cause cracks and active material shedding and powdering.

[0050] In addition, the inventors have found that the winding stress generated by the winding core will cause extrusion and stretching at various positions of the electrode and the diaphragm; during the charging and discharging process of the battery, the thickness of the electrode expands, and the extrusion and stretching of the core will be further aggravated. Due to the winding stress of the battery cell and the cyclic expansion and stretching of the electrode, the diaphragm will undergo tensile deformation and the thickness of the diaphragm will become thinner. The active material layer of the electrode in the inner part of the core with a smaller curvature radius is prone to powder loss. Therefore, the fallen dust can easily pierce the corresponding thinner diaphragm and contact another electrode with opposite polarity, thereby causing a battery short circuit.

[0051] In response to the above technical problems, an embodiment of the present application provides a winding core, in which the diaphragm and the first pole piece are fixed to form a composite part, and a convex portion is arranged on the composite part. The overall composite part is uneven, which improves the elastic deformation capacity of the pole piece and the diaphragm of the winding core, increases the deformation space of the pole piece and the diaphragm, and can relieve the internal stress and expansion force of the winding core after winding when the battery cyclically expands, disperse the expansion force on the pole piece or the diaphragm, avoid stress concentration on the pole piece or the diaphragm, and thus prevent the problem of tensile deformation and thinning of the diaphragm or cracks on the pole piece or powder loss of the active material layer; and the composite part belongs to the same whole. During the battery cyclic expansion process, since convex portions are formed on both the diaphragm and the pole piece, and the first pole piece and the diaphragm are bonded together, the first pole piece and the diaphragm can be extended at the same frequency under the premise of effectively dispersing the internal stress and expansion force, thereby preventing frictional powder loss caused by the mismatch of the extension of the pole piece and the diaphragm.

[0052] In order to make the above-mentioned purposes, features and advantages of the embodiments of the present application more obvious and understandable, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of this application.

[0053] Combination Figures 1 to 5 The winding core provided in the embodiment of the present application includes a first pole piece 110, a diaphragm 120 and a second pole piece 130. The first pole piece 110, the diaphragm 120 and the second pole piece 130 are stacked and wound together, and the diaphragm includes a first diaphragm layer and a second diaphragm layer; the first diaphragm layer is located between the first pole piece 110 and the second pole piece 130; the first pole piece 110 is located between the first diaphragm layer and the second diaphragm layer; the first diaphragm layer includes a first part extending beyond the first pole piece 110, and the second diaphragm layer includes a second part extending beyond the first pole piece 110, and the first part and the second part are adhered to each other.

[0054] The first diaphragm layer, the first pole piece and the second diaphragm layer form a composite part; the composite part includes a first surface close to the center of the winding core and a second surface away from the center of the winding core.

[0055] The composite part is provided with a plurality of convex parts, and the convex parts are bent and protruded from the first surface toward the second surface.

[0056] In a specific example, the composite part may be formed with protrusions by, for example, simultaneously embossing the first diaphragm layer, the first pole piece, and the second diaphragm layer with a roller having protrusions of dots or stripes, thereby forming the protrusions.

[0057] In this case, by bonding the first part and the second part of the diaphragm, the first diaphragm layer and the second diaphragm layer are respectively bonded to the first pole piece to form a composite part, thereby preventing the pole piece from turning inward, while reducing the shrinkage of the diaphragm at high temperature, and reducing the risk of short circuit caused by contact between the positive and negative pole pieces;

[0058] In addition, a plurality of protrusions are provided on the composite part, and the protrusions are bent and protrude from the first surface toward the second surface. The composite part forms a space for accommodating electrolyte between the protrusions of the composite part and the second pole piece, thereby increasing the storage space for the electrolyte and improving the wetting ability of the electrolyte in this area, thereby avoiding abnormal situations such as insufficient electrolyte and poor wetting between pole piece layers.

[0059] Furthermore, the overall shape of the composite part is uneven, which improves the elastic deformation capacity of the pole piece and diaphragm of the winding core and increases the deformation space of the pole piece and diaphragm. When the battery expands during a cycle, the internal stress and expansion force of the winding core can be relieved, and the expansion force on the pole piece or diaphragm can be dispersed, thereby avoiding stress concentration on the pole piece or diaphragm, thereby eliminating the problem of tensile deformation and thinning of the diaphragm or cracks on the pole piece or powder loss of the active material layer. Moreover, the composite part belongs to the same whole. During the battery cycle expansion process, since convex portions are formed on both the diaphragm and the pole piece, and the first pole piece and the diaphragm are bonded together, the first pole piece and the diaphragm can extend at the same frequency under the premise of effectively dispersing the internal stress and expansion force, thereby preventing frictional powder loss caused by the mismatch in the extension of the pole piece and the diaphragm.

[0060] In some specific embodiments, the first electrode sheet may be a positive electrode sheet, and the first and second diaphragm layers of the diaphragm and the positive electrode active material layer of the positive electrode sheet are bonded by hot pressing, high-temperature rolling, high-temperature crosslinking or ultraviolet light crosslinking, and the first part of the first diaphragm layer and the second part of the second diaphragm layer are bonded to each other, so that the positive electrode sheet diaphragm forms a bag-shaped composite part, which can prevent the positive electrode sheet from being damaged after falling; in another embodiment, the first electrode sheet may be a negative electrode sheet, and the first and second diaphragm layers of the diaphragm and the negative electrode active material layer of the negative electrode sheet are bonded by hot pressing, high-temperature rolling, high-temperature crosslinking or ultraviolet light crosslinking, and the first part of the first diaphragm layer and the second part of the second diaphragm layer are bonded to each other, so that the negative electrode sheet diaphragm forms a bag-shaped composite part.

[0061] In some embodiments, the composite part also includes a plurality of recessed portions corresponding to the plurality of protrusions, and the recessed portions are recessed from the first surface toward the second surface of the composite part. Considering that the winding stress of the inner layer of the winding core and the small spacing between the inner layer pole pieces make it difficult for the electrolyte to penetrate, by forming a recessed portion recessed from the first surface toward the second surface, the recessed portion can play a role in accommodating the electrolyte and increase the liquid retention capacity of the inner layer of the battery cell.

[0062] In some embodiments, the first pole piece includes a straight section and an arc section, and the convex portion is arranged on the straight section and / or the arc section. By such arrangement, in addition to increasing the storage space of the electrolyte and improving the infiltration capacity of the electrolyte in the corresponding area; when the convex portion is located in the arc section, the gap between the first pole piece and the second pole piece can be increased, the bending radius of the arc area can be increased, and the extrusion stress between the pole pieces can be reduced; and the convex portion can offset part of the expansion stress of the second pole piece on the first pole piece, thereby preventing the first pole piece from being broken or powdered due to a large stress, and reducing the probability risk of self-discharge.

[0063] In some embodiments, the protrusion height of the convex portion of the straight section is greater than the protrusion height of the convex portion of the arc section. Considering that the straight section is longer and has a larger force-bearing area, while the area of ​​the arc section is smaller, if the protrusion height of the convex portion of the arc section is too large, the arc section is prone to breakage due to excessive force during the embossing process to form the convex portion.

[0064] In some embodiments, the straight section of the first pole piece is bonded to the first diaphragm layer and the second diaphragm layer respectively; the arc section of the first pole piece is not bonded to the first diaphragm layer or the second diaphragm layer.

[0065] With such a design, when the first diaphragm layer and the second diaphragm layer of the diaphragm 120 are thermally composited with the first pole piece 110, the thermal composite area avoids the arc section and is composited only in the straight section, thereby preventing the diaphragm and the first pole piece from being thermally composited and bonded at the arc section. In the case where the diaphragm and the first pole piece are thermally composited and bonded at the arc section, the diaphragm and the first pole piece are subjected to the combined action of the winding stress and the pole piece expansion force during the winding process, and are restrained by each other, which may easily lead to the composite part of the arc section being torn, that is, the diaphragm and the first pole piece are separated, or the diaphragm or the first pole piece is broken.

[0066] In some embodiments, the protrusion includes a first protrusion located on the first diaphragm layer, a second protrusion located on the first pole piece, and a third protrusion located on the second diaphragm layer. For example, the first protrusion, the second protrusion, and the third protrusion can be directly formed by embossing on the composite part by roller embossing.

[0067] In some embodiments, the vertical distance between the vertex of the second convex portion and the first surface is 3-50 microns; for example, h1 can be one of 3μm, 3.7μm, 5μm, 9μm, 10μm, 12μm, 23μm, 34μm, 36μm, 40μm, 43μm and 47μm. Alternatively, h1 can be any point value within the range of greater than or equal to 3μm and less than or equal to 50μm.

[0068] In this way, it can be ensured that while the protrusion satisfies the requirements of providing space for storing electrolyte and absorbing the expansion stress of the electrode, it can be avoided that the first electrode is easily broken due to excessive force during the formation of the protrusion due to the height of the protrusion being too high, and it can also be ensured that the expansion stress of the second electrode cannot be fully absorbed through deformation and sufficient liquid storage space cannot be provided due to the height of the protrusion being too low.

[0069] In some embodiments, the radius of curvature R1 of the second convex portion is 0.5 mm ≤ R1 ≤ 8 mm; for example, R1 may be one of 0.5 mm, 0.5 mm, 1.5 mm, 2.4 mm, 2.9 mm, 3.1 mm, 3.7 mm, 4.8 mm, 5.5 mm, 6.7 mm, 7.1 mm and 7.5 mm. Alternatively, R1 may be any value within a range of greater than or equal to 0.5 mm and less than or equal to 8 mm.

[0070] By limiting the curvature radius of the second convex portion of the first pole piece, the projection area of ​​the convex portion can be adjusted. When it is too small, the projection area of ​​the convex portion is too small, and the convex portion is too sharp. When it abuts against the diaphragm, it is easy to cause damage to the first pole piece and the diaphragm, and the deformation space of the first pole piece is small, and the improvement effect is not good. When it is too large, the projection area of ​​the convex portion is too large, so that the convex portion is easy to deform excessively under the action of the extrusion force, the extension force and the cyclic expansion force during the formation process.

[0071] In some embodiments, the spacing L1 between adjacent second protrusions is 3 mm ≤ L1 ≤ 10 mm. For example, L1 can be one of 3 mm, 3.5 mm, 4 mm, 4.7 mm, 5 mm, 5.2 mm, 6 mm, 6.7 mm, 7 mm, 7.7 mm, 8 mm, 8.6 mm, 9.2 mm, and 9.7 mm. Alternatively, L1 can be any value within a range of greater than or equal to 3 mm and less than or equal to 10 mm.

[0072] When the spacing between the convex parts is less than 2mm, the convex points of the processing roller are too dense. In the process of forming the convex parts, the extension of the pole piece cannot meet the density of the convex parts, which easily makes the height of the convex parts unable to meet the requirements, resulting in less deformation space for the first pole piece. In addition, the convex parts are too dense, which makes it easy for the pole piece to break during the formation of the convex parts. When the spacing is greater than 10mm, the convex points of the processing roller are too sparse, the convex parts are too dispersed, and the supporting area of ​​the convex parts is insufficient, thereby failing to improve the electrolyte infiltration effect. In some embodiments, the composite part is spaced apart along its length direction to form at least two spaced-apart convex areas; the convex area includes a plurality of the convex parts;

[0073] In some embodiments, the composite part also includes a pole ear area located between the two raised areas. Along the length direction of the first pole piece, the distance from the edge of the pole ear area to the adjacent raised area is 1.5-20 mm; the distance from the edge of the pole ear area 150 to the adjacent raised area 140 is 1.5 mm, or the distance from the edge of the pole ear area 150 to the adjacent raised area 140 is 11 mm, or the distance from the edge of the pole ear area 150 to the adjacent raised area 140 is 20 mm. In this way, by maintaining a certain distance between the pole ear area 150 and the raised area 140, interference with the pole ear can be effectively reduced, and the pole ear can be prevented from being subjected to excessive force during the formation of the raised area 140, thereby compressing the current collector under the pole ear, thereby causing the pole ear to be poorly welded or leaking.

[0074] In some embodiments, along the width direction of the first pole piece, the distance from the raised area to the edge of the adjacent composite part is 0.5-20 mm; for example, the distance from the raised area 140 to the edge of the adjacent composite part 100 is 0.5 mm, or the distance from the raised area 140 to the edge of the adjacent composite part 100 is 10 mm, or the distance from the raised area 140 to the edge of the adjacent composite part 100 is 20 mm. In this way, it is possible to avoid the protrusion being too close to the edge of the composite part 100, which would weaken the bonding force between the first part and the second part, thereby causing separation between the first part and the first pole piece or the second part and the first pole piece, and to achieve the maximum area layout of the raised area 140.

[0075] In some embodiments, along the length direction of the first pole piece, the distance from the protruding area to the edge of the adjacent composite part is 3-50 mm. Exemplarily, the distance from the protruding area 140 to the edge of the adjacent composite part 100 is 3 mm, or the distance from the protruding area 140 to the edge of the adjacent composite part 100 is 26 mm, or the distance from the protruding area 140 to the edge of the adjacent composite part 100 is 50 mm, so as to avoid the protrusion being too close to the edge of the composite part 100, so that the bonding force between the first part and the second part becomes weak, thereby causing the first part and the first pole piece or the second part and the first pole piece to separate, and also to avoid the protrusion density being too low to affect the improvement effect of the composite part 100 on the electrolyte infiltration.

[0076] In some embodiments, it is characterized in that the ratio of the vertical distance between the second protrusion of the first pole piece and the first surface to the thickness of the first pole piece is in the range of 10% to 60%. In one embodiment, the first pole piece is a positive pole piece, and the ratio of the vertical distance between the second protrusion of the positive pole piece and the first surface to the thickness of the first pole piece is in the range of 10% to 60%, preferably 15-50%; in one embodiment, the first pole piece is a negative pole piece, and the ratio of the vertical distance between the second protrusion of the negative pole piece and the first surface to the thickness of the negative pole piece is in the range of 10-50%, preferably 15-30%.

[0077] In some embodiments, along the thickness direction of the composite part 100, the ratio of the distance between the centers of two adjacent second protrusions to the diameter of the second protrusions is in the range of 1.05-3. For example, it can be 1.05, 1.1, 2, 2.5, 3. By limiting the spacing of the protrusions and the diameter of the protrusions, the density of the protrusions is ensured to prevent the pole piece from being broken due to excessive force during the formation of the protrusions due to excessive density, or the improvement effect of electrolyte infiltration is poor due to insufficient density.

[0078] In some embodiments, the tensile strength of the diaphragm 120 is greater than or equal to 2500kgf / cm2; for example, the tensile strength of the diaphragm 120 is 2500kgf / cm2, or the tensile strength of the diaphragm 120 is 2800kgf / cm2; thereby preventing the tensile strength of the composite part from being changed due to the low tensile strength of the diaphragm during the charge and discharge process; or, the puncture strength of the diaphragm 120 is greater than or equal to 260gf, for example, the puncture strength of the diaphragm 120 is 260gf, or the puncture strength of the diaphragm 120 is 280gf, thereby improving the ability of the diaphragm to prevent puncture by foreign objects, thereby preventing the possibility of rupture of the diaphragm of the composite part during the puncture test; in more examples, the tensile strength and puncture strength of the diaphragm 120 simultaneously meet the above conditions, thereby improving the ability of the composite part to resist stretching, extrusion and puncture by foreign objects, and reducing the possibility of damage to the diaphragm 120 and the electrode after the composite part 100 is formed during the embossing process or in the subsequent test experiments.

[0079] In some embodiments, the first pole piece includes a first current collector, the first pole piece is a positive pole piece, and the tensile strength of the first current collector is greater than or equal to 200Mpa; in another embodiment, the first pole piece is a negative pole piece, and the tensile strength of the second current collector is greater than or equal to 550Mpa. By using a corresponding current collector with a strong tensile strength, the tensile resistance of the first pole piece of the composite part is enhanced, thereby not only avoiding the risk of damage to the first pole piece in the process of forming the convex portion, but also ensuring the synchronous extension of the first pole piece and the diaphragm in the composite part, preventing the first pole piece and the diaphragm from separating during the deformation process.

[0080] In some embodiments, the first electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer. In a nitrogen environment, the weight loss rate of the positive electrode active material layer from 35° to a temperature range of 300°C to 600°C is ρ, and ρ satisfies: 1.1% to 6%. By controlling the weight loss rate, the structural stability of the positive electrode active material layer at high temperatures is ensured, and its normal function at high temperatures is ensured. Moreover, the weight loss rate refers to the decomposition of the binder (PVDF) in the positive electrode active material layer by heat, resulting in weight loss. By controlling within this range, the positive electrode active material layer can be fully utilized without losing powder.

[0081] In some embodiments, the positive electrode active material layer includes a positive electrode active material and a binder, wherein the binder accounts for 0.5%-2% by mass of the positive electrode active material layer, preferably, the binder accounts for 0.8%-1.5% by mass of the positive electrode active material, and exemplarily, the binder accounts for 0.5% by mass of the positive electrode active material, or, the binder accounts for 2% by mass of the positive electrode active material, or, the binder accounts for 1.5% by mass of the positive electrode active material, or, the binder accounts for 1.5% by mass of the positive electrode active material. The percentage is 0.8%, and the range of the adhesive content is reasonably controlled to prevent the adhesive content from being too small, the positive electrode active material and the foil from having low bonding strength, the positive electrode sheet being easily powdered due to excessive force during winding or in the process of forming a convex portion, and the adhesive content being too large, the overall elastic modulus of the positive electrode sheet increasing, the toughness of the electrode sheet becoming poor, and the electrode sheet being easily damaged due to excessive force and deformation during the process of forming a convex portion. Preferably, the adhesive is polyvinylidene fluoride (PVDF), which has a higher elastic modulus as a binder and has better toughness after being made into the composite part 100.

[0082] Exemplarily, the first pole piece 110 is a positive electrode, and the first pole piece 110 includes a first current collector and a first active material layer disposed on the surface thereof, i.e., a positive electrode active material layer. The material used may be LiCoO2, LiNiO2, LiMn2O4, LiCo1-yMyO2, LiNi1-yMyO2, LiMn2-yMyO4 or LiNixCoyMnzM1-xy-zO2, wherein M is selected from at least one of Fe, Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V or Ti, and 0≤y≤1, 0≤x≤1, 0≤z≤1, x+y+z≤1. The material of the above-mentioned positive electrode active material layer may be doped and / or coated.

[0083] Further, the positive electrode active material layer also includes a binder and a conductive agent. Exemplarily, the binder in the positive electrode active material layer may include polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, a polyamide, a polyacrylonitrile, a polyacrylate, a polyacrylic acid, a polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, a polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene; the conductive agent may include at least one of conductive carbon black, acetylene black, ketjen black, flake graphite, graphene, carbon nanotubes or carbon fibers.

[0084] In some embodiments, the first electrode sheet is a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer includes a silicon-carbon composite material and / or a silicon-oxygen composite material, and the percentage of silicon in the negative electrode active layer is 5%-50%. The silicon-carbon composite material may include a porous carbon matrix, silicon grains located in the pores of the porous silicon matrix, and a carbon layer located on the surface of the porous carbon matrix. The material of the carbon layer may be shaped carbon or amorphous carbon.

[0085] In some embodiments, the carbon layer may include openings arranged corresponding to the pores of the porous silicon substrate.

[0086] In this way, by setting openings on the carbon layer corresponding to the pores of the porous silicon substrate, the wettability of the electrolyte to the negative electrode active material can be improved, while the expansion performance of silicon can be reduced, the cycle life of the battery cell can be improved, and the service life of the battery can be increased.

[0087] In some embodiments, the material of the negative electrode active layer 31 may also include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, graphene, soft carbon, hard carbon, soft carbon-coated graphite material, and hard carbon-coated graphite material.

[0088] In some embodiments, the specific surface area of ​​the silicon-carbon composite material is 0.5 m 2 / g-10m 2 / g, for example, the specific surface area of ​​the silicon-carbon composite material can be 0.5m 2 / g, 0.9m 2 / g, 1.3m 2 / g, 1.5m 2 / g, 1.85m 2 / g, 2.0m 2 / g, 2.3m 2 / g, 2.7m 2 / g, 3.2m 2 / g, 3.6m 2 / g, 3.8m 2 / g, 4.6m2 / g, 4.8m 2 / g, 5.1m 2 / g, 5.4m 2 / g, 5.8m 2 / g, 6.1m 2 / g, 6.5m 2 / g, 6.8m 2 / g, 7.2m 2 / g, 7.5m 2 / g, 7.8m 2 / g, 8.3m 2 / g, 8.9m 2 / g, 9.4m 2 / g and 9.9m 2 Alternatively, the specific surface area of ​​the silicon-carbon composite material may be greater than or equal to 0.5 m 2 / g and less than or equal to 10m 2 Any value within the range of / g.

[0089] In this way, by controlling the specific surface area in the silicon-carbon composite material, the solid electrolyte interface (SEI) film during the charging process can be reduced, and the cycle performance and service life can be improved. It can avoid the situation where the thickness of the SEI film is too small due to the small specific surface area, thereby failing to effectively isolate the electrolyte and the negative electrode active layer 31. It can also avoid the SEI film being too large due to the large specific surface area, and can reduce the impact of the SEI film being too thick on the capacity and efficiency of the battery.

[0090] In some embodiments, the particle size Dv50 of the silicon-carbon composite material or the silicon-oxygen composite material is 6μm-15μm. For example, the particle size of the silicon-doped graphite is 5μm, or the particle size of the silicon-doped graphite is 15μm. In this way, the overall volume energy density of the core can be improved. The smaller negative electrode particle size means more inter-particle interfaces, which helps to increase the active sites for lithium ion embedding and extraction, thereby improving the energy density of the battery; however, too small anode particle size may also increase the contact resistance between particles, affecting the battery cycle performance.

[0091] Thus, by controlling the particle size of the silicon-carbon composite material within the above range, it is possible to avoid the situation where the specific surface area of ​​the silicon particles is increased when the particle size is too small, thereby increasing the side reactions. It is also possible to avoid the problem where the silicon particles are easily expanded too much when the particle size is too large, thereby blocking the pores of the porous carbon matrix and affecting the infiltration of the electrolyte.

[0092] The average sphericity of the silicon-carbon material is in the range of 0.5-1, for example, the average sphericity can be one of 0.6, 0.7, 0.8 and 0.9. Compared with non-spherical particles, the higher the sphericity, the closer the shape is to a sphere, so that when its volume expands, the impact on the structure of the negative electrode sheet 30 is smaller, and the overall structural stability of the negative electrode sheet 30 can be maintained during expansion.

[0093] In addition, spherical particles can improve the mechanical strength and stability of the material and reduce the stress concentration between particles caused by expansion, thereby reducing the risk of mechanical wear and damage to the material during the cycle.

[0094] In some embodiments, the powder resistivity of the silicon-carbon composite material ranges from 0.1Ω·cm to 1000Ω·cm. For example, the powder resistivity of the silicon-carbon composite material may be one of 0.1Ω·cm, 0.9Ω·cm, 1.2Ω·cm, 1.3Ω·cm, 1.8Ω·cm, 2.7Ω·cm, 4.6Ω·cm, 7.8Ω·cm, 11Ω·cm, 25Ω·cm, 38Ω·cm, 60Ω·cm, 100Ω·cm, 200Ω·cm, 300Ω·cm, 400Ω·cm, 500Ω·cm, 600Ω·cm, 700Ω·cm, 800Ω·cm, 900Ω·cm and 1000Ω·cm. Alternatively, the powder resistivity of the silicon-carbon composite material may be any point value within the range of greater than or equal to 0.1Ω·cm and less than or equal to 1000Ω·cm.

[0095] In some embodiments, the silicon content in the silicon-carbon composite material may be 30%-75%, for example, the silicon content in the silicon-carbon composite material may be one of 30%, 35%, 41%, 45%, 49%, 51%, 55%, 59%, 61%, 64%, 71% and 84%. Alternatively, the silicon content in the silicon-carbon composite material may be any point value within the range of greater than or equal to 30% and less than or equal to 75%.

[0096] In this way, it is possible to avoid excessive silicon content in the negative electrode active layer 31 causing excessive expansion of the negative electrode sheet, thereby deforming the overall structure of the silicon-carbon particles, and to avoid too little silicon content reducing the energy density of the battery.

[0097] Further, the negative electrode active material layer may also include a conductive agent and / or a binder. Exemplarily, the conductive agent in the negative electrode active material layer may include at least one of carbon black, acetylene black, Ketjen black, flake graphite, graphene, carbon nanotubes, carbon fibers, or carbon nanowires; the binder in the negative electrode active material layer may include at least one of carboxymethyl cellulose CMC, polyacrylic acid, polyacrylic acid salt, polyacrylic acid ester, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, and polyurethane resin.

[0098] In some embodiments, the absolute plastic deformation rate of the diaphragm 120 is ε1=50%-1600%, for example, the absolute plastic deformation rate ε1 of the diaphragm 120 is 50%, or, the absolute plastic deformation rate ε1 of the diaphragm 120 is 1600%. Further, the relative plastic deformation rate of the diaphragm 120 is ε2=70%-90%, for example, the relative plastic deformation rate ε2 of the diaphragm 120 is 70%, or, the relative plastic deformation rate ε2 of the diaphragm 120 is 90%.

[0099] It should be noted that the reference Figure 4 , the diaphragm 120 is stretched to a maximum length L1, the broken diaphragm 120 is butt-jointed and flattened along the fracture, and its length L2 in the natural state is tested, the elastic deformation = L1-L2, the plastic deformation = L2-L0, the total deformation = elastic deformation + plastic deformation, the absolute plastic deformation rate ε1 of the diaphragm 120 = (L2-L0) / L0×100% and the relative plastic deformation rate ε2 = (L2-L0) / (L1-L0)×100%, it can be understood that plastic deformation is a permanent deformation and no rebound will occur. During the lithium-ion battery puncture test, the greater the plastic deformation of the diaphragm 120, the greater the degree to which the diaphragm 120 extends with the nail and produces permanent deformation, and the better the wrapping effect on the nail, thereby maintaining the isolation effect of the diaphragm 120 on the positive and negative electrodes and reducing the probability of lithium-ion battery failure; conversely, if the elastic deformation accounts for a large proportion, even if the diaphragm 120 extends during the puncture process, the diaphragm 120 will shrink significantly after being punctured, thereby weakening the isolation effect of the diaphragm 120 on the positive and negative electrodes.

[0100] In this way, the absolute plastic deformation rate and relative plastic deformation rate of the diaphragm 120 are within a certain reasonable range. When penetrated by hard objects such as steel nails, the diaphragm 120 around the steel nails will extend along with the steel nails, eventually forming a wrapping effect on the steel nails, thereby reducing the probability of internal short circuits.

[0101] Furthermore, the diaphragm 120 in the embodiment of the present application includes a ceramic layer, a base film layer and an adhesive layer. In particular, the outermost layer of the diaphragm 120 must be an adhesive layer, and other structures may be ceramic layers, base film layers or adhesive layers. Exemplarily, the specific structural composition of the diaphragm 120 may be an adhesive layer-ceramic layer-base film layer-adhesive layer, or, it may also be an adhesive layer-base film layer-adhesive layer, or, it may be an adhesive layer-ceramic layer-base film layer-ceramic layer-adhesive layer. The thickness of the diaphragm 120 is 4 to 25 μm, preferably 6 to 15 μm. For example, the thickness of the diaphragm 120 is 4 μm, or, the thickness of the diaphragm 120 is 25 μm, or, the thickness of the diaphragm 120 is 15 μm, or, the thickness of the diaphragm 120 is 6 μm.

[0102] Among them, exemplary, the base membrane layer of the diaphragm 120 can be selected from one of polyethylene, polypropylene, polyamide, polyester, polyether, polyvinyl chloride, polymethyl methacrylate, polytetrafluoroethylene, polyether sulfone, polyimide, polyether ether ketone, polystyrene, polyurethane, fluorinated polymer, silicone rubber, glass fiber, aramid, and ceramic composite materials.

[0103] It should be noted that in the embodiment of the present application, the diaphragm 120 is compounded with the electrode. If the contact is poor, the transmission of lithium ions is easily hindered, affecting the charge and discharge rate, and may also cause problems such as lithium precipitation. Therefore, an adhesive layer is provided to improve the adhesion between the diaphragm 120 and the electrode. The adhesive in the adhesive layer of the diaphragm 120 can be selected from at least one of polyacrylate, polyvinyl alcohol, polyimide, polyether ketone, polyether sulfide, polytetrafluoroethylene, polymethyl methacrylate, polystyrene, polyurethane and polyethylene terephthalate.

[0104] Among them, the diaphragm 120 can be hot pressed with the first pole piece 110 by hot pressing, high-pressure rolling, high-temperature crosslinking or ultraviolet light crosslinking, so that the adhesive layer on the surface of the diaphragm 120 and the active material or adhesive on the surface of the first pole piece 110 are connected by chemical bonds or physical bonds, thereby achieving a fixed connection between the diaphragm 120 and the first pole piece 110, thereby forming a composite part 100.

[0105] In a second aspect, an embodiment of the present application provides a battery, which includes a core provided by any embodiment of the first aspect and a packaging film covering the core.

[0106] In some embodiments, a recessed portion is provided on the packaging film, the recessed portion is recessed toward the side away from the core body, and the recessed portion has a depth of 10-35 μm, for example, the recessed depth may be 10, 12, 15, 20, 30, 35 μm. For example, the surface of the packaging film may be punched with a mold, and the inner surface of the aluminum-plastic film may be rolled and embossed to form the recessed portion, which may improve the electrolyte storage capacity inside the packaging film, enhance the electrolyte wettability of the entire battery cell, and enhance the overall liquid retention capacity of the battery cell.

[0107] In some embodiments, the packaging film includes a PP layer, an aluminum foil layer, and a nylon layer that are stacked, the PP layer is located on a side of the aluminum foil layer close to the winding core, and the PP layer is provided with the recessed portion.

[0108] In some embodiments, the ratio of the depression depth of the depression to the thickness of the aluminum foil layer is less than or equal to 40%. By controlling this range, it is mainly to prevent the aluminum foil layer from being easily crushed by excessive force when the depression depth of the depression is too large; in other embodiments, the projection of the depression is circular, and the diameter of the circular embossed portion is 0.8-2mm; exemplarily, the diameter of the circular embossed portion is 0.8mm, or the diameter of the circular embossed portion is 2mm.

[0109] In some embodiments, a plurality of recessed portions are disposed on the packaging film to form a recessed area, and the distance between the recessed area and the outer edge of the packaging film is 1-2 mm. For example, the distance between the recessed area and the outer edge of the packaging film is 1 mm, or the distance between the recessed area and the outer edge of the packaging film is 2 mm. Figure 3 , the distance between the recessed area and the outer edge of the packaging film is A1=A2=A3=A4=1-2mm; further, the density of the recessed parts in the recessed area, taking a 20*20mm film shell for counting, the number of recessed parts is in the range of 100-120; if the distance between the recessed area and the four sides of the inner pit of the film shell is too close, the thickness of the aluminum layer of the fillet around the film shell will be reduced, resulting in corner breakage during the battery cell cycle and battery swelling and leakage; if the distance between the recessed area and the four sides of the inner pit of the film shell is too far, the embossing area is small, and the effect of improving the battery liquid retention is not significant.

[0110] In some embodiments, within a unit area, the ratio of the number of the recessed portions to the area of ​​the side surface of the packaging film is 0.25-0.5:1. Exemplarily, the ratio of the number of the embossed portions to the area of ​​the side surface of the packaging film is 0.25:1, or the ratio of the number of the embossed portions to the area of ​​the side surface of the packaging film is 0.5:1.

[0111] Example 1

[0112] The winding core and battery provided in this embodiment include the following steps:

[0113] Preparation of the positive electrode sheet (first electrode sheet): lithium cobalt oxide, polyvinylidene fluoride, carbon black, and carbon tubes in a mass ratio of 98:1.0:0.5:0.5 are added to N-methylpyrrolidone (solvent) as positive electrode active materials, and the positive electrode slurry is obtained after dispersion. Aluminum foil is used as a carrier, and the positive electrode slurry is coated, rolled and cut to obtain a positive electrode sheet, wherein the thickness of the aluminum foil is 9 μm.

[0114] Preparation of the negative electrode sheet (second electrode sheet): Graphite, silicon carbon, styrene-butadiene rubber, lithium polyacrylate and carbon black in a mass ratio of 91.65:5.85:1.0:1.0:0.5 (6wt% silicon doping amount), negative electrode active material Dv50=12μm, are added into deionized water and dispersed to obtain a negative electrode slurry. Copper foil is used as a carrier, and the negative electrode slurry is coated, rolled and cut to obtain a negative electrode sheet.

[0115] The diaphragm structure is set to bonding layer-ceramic layer-base film layer-adhesive layer, the base film thickness is 5μm, the single-sided ceramic layer thickness is 1μm, and the single-sided adhesive layer is 0.75μm; in the surface area of ​​the positive electrode sheet and the negative electrode sheet, the temperature is 80°C and the pressure is 1.0Mpa, and the adhesive layer of the diaphragm is hot-pressed onto the positive electrode sheet to form a composite part; the embossing parameters of the composite part are as follows: the depth of the positive electrode embossing Csd=110μm, the thickness of the positive electrode sheet Ch=98μm, and further, Csd / Ch=Gc, wherein Gc=112%; the spacing between the middle centers of two adjacent protrusions is W=1.5mm, the diameter of the protrusion is 1mm, and W / R1=1.5; the composite part and the negative electrode sheet are wound to form a winding core.

[0116] The total thickness of the aluminum-plastic film of the packaging layer of the roll core is 86μm, the thickness of the aluminum layer is 35μm, and the film shell after punching is embossed with a convex portion from the polypropylene (PP) layer to the aluminum layer, wherein the depth of a single embossed convex portion Sd2=13μm; the diameter of a single embossed convex portion R2=1.2mm; the upper, lower, left and right distances between the embossing and the inner pit of the punched film shell A1=A2=A3=A4=1.8mm; the density of the embossing, taking a 20*20mm film shell for counting, the number of embossings is 110.

[0117] The lithium-ion battery of this embodiment is obtained by packaging, injecting, forming and sorting the core.

[0118] Example 2

[0119] On the basis of Example 1, the composite structure of the winding core is only the bonding of the negative electrode sheet (second electrode sheet) and the separator.

[0120] Example 3

[0121] Based on Example 1, no convex portion is provided in the composite part structure in the winding core.

[0122] Example 4

[0123] On the basis of Example 1, in the positive electrode sheet, the content of the binder (PVDF) in the positive electrode active material is changed to 0.5 wt %.

[0124] Example 5

[0125] On the basis of Example 1, in the positive electrode sheet, the content of the binder (PVDF) in the positive electrode active material is changed to 2 wt %.

[0126] Comparative Example 1

[0127] On the basis of Example 1, no convex part is arranged on the composite part and the aluminum-plastic film.

[0128] Comparative Example 2

[0129] On the basis of Example 1, in the positive electrode sheet, the content of the binder (PVDF) in the positive electrode active material is changed to 2.1 wt %.

[0130] Comparative Example 3

[0131] On the basis of Example 1, in the positive electrode sheet, the content of the binder (PVDF) in the positive electrode active material is changed to 2.5 wt %.

[0132] Comparative Example 4

[0133] On the basis of Example 1, copper foil and aluminum foil with tensile strengths of 450 MPa and 190 MPa respectively were used as negative electrode and positive electrode current collectors.

[0134] Comparative Example 5

[0135] On the basis of Example 1, copper foil and aluminum foil with tensile strengths of 400 MPa and 170 MPa respectively were used as negative electrode and positive electrode current collectors.

[0136] Comparative Example 6

[0137] On the basis of Example 1, in the positive electrode sheet, the content of the binder (PVDF) in the positive electrode active material is changed to 0.4 wt %.

[0138] Table 1 shows the performance parameters of the separators in Examples 1-5 and Comparative Examples 1-6 and the physical parameters of the protrusions on the composite part including the separator.

[0139] It should be noted that the parameter determination methods in Table 1 include:

[0140] (1) Diaphragm puncture strength test: Use a WD-D3 electronic universal testing machine with a needle radius of R = 0.5 mm for the puncture fixture. Take a diaphragm sample with a length and width of ≥ 80 mm * 80 mm and install it in the fixture. Adjust the speed to 100 mm / min. After the diaphragm is punctured, it will automatically stop running and record the maximum value.

[0141] (2) Test of diaphragm tensile strength, absolute plastic deformation rate and relative plastic deformation rate: Combined Figure 4 The diaphragm is cut into strips of 80-100 cm in length and 1.5 cm in width using a sample preparation device. The gauge length of the two fixtures of the WD-D3 electronic universal testing machine is adjusted to 50 mm. An area with a length of L0 = 50 mm is selected, and marking lines are made at both ends of the area. The diaphragm is stretched at a speed of 100 mm / min, and the maximum strength displayed is regarded as the tensile strength of the diaphragm; it is stretched to fracture, and the maximum length L1 reached by the stretching is recorded. Then the broken diaphragm is butt-jointed and flattened along the fracture, and its length L2 in the natural state is tested. The absolute plastic deformation rate ε1 = (L2-L0) / L0×100% and the relative plastic deformation rate ε2 = (L2-L0) / (L1-L0)×100% of the diaphragm in a certain direction are calculated.

[0142] (3) Dimensional measurement of the composite part and the embossed convex part of the aluminum-plastic film: Use an elemental analysis microscope to test, take photos at a magnification of 200 times, and test the diameter R of a single convex part and the depression depth Sd of the convex part, in μm; the spacing W between the centers of a single adjacent convex part, in mm; test the distances S1 and S2 between the convex part and the upper and lower edges of the composite part, and the distances S3 and S4 between the convex part and the head and tail edges of the composite part, in mm, at a magnification of 50 times; test the distances A1 and A2 between the upper and lower edges of the inner pit of the convex part of the aluminum-plastic film after embossing and punching, and the left and right distances A3 and A4 of the inner pit of the aluminum-plastic film after embossing and punching, in mm, at a magnification of 50 times.

[0143] (4) Thickness of positive electrode sheet, negative electrode sheet and diaphragm: Under the protection of liquid nitrogen, use an ion grinder to cut the cross section of the sample, use a scanning electron microscope energy spectrometer, select the electrode magnification of 500x-1kx, and the diaphragm discharge rate of 5kx~10kx, find the cross-sectional positions of the foil and paste, base film, ceramic layer and bonding layer respectively, and take the average value of the thickness at 5 different positions of the test sample.

[0144] (5) Particle size test of negative electrode graphite doped with silicon powder (Dv50 / Dv90): The particle size distribution was tested using a Malvern laser particle size tester.

[0145] (6) Test of tensile strength σ and elongation at break δ of positive and negative electrode foils: Take copper and aluminum foils, cut them into strips with a length of 60-70 cm and a width of 1.5 cm, and stretch the copper foil at a stretching rate of 50 cm / min and the aluminum foil at a stretching rate of 10 cm / min in a tensile testing machine. The maximum strength displayed is regarded as the tensile strength of the copper foil, recorded as σ a ; The tensile strength of aluminum foil is denoted as σ c .

[0146] (7) Test of binder content in positive electrode formula (first electrode): Using a thermogravimetric analyzer (TGA), with a sample mass of 5-20 mg, the temperature was raised to 1000°C at a heating rate of 10°C / min in a nitrogen atmosphere to obtain a thermogravimetric curve. Thermogravimetric curve: A curve in which the data measured by thermogravimetry are expressed as mass (or mass fraction) versus temperature or time. The binder content can be obtained by calculating the weight loss ratio of the powder between 200-600°C.

[0147] (8) Pole piece damage degree test: Take a 30×30 cm pole piece for penetration test, apply the penetrant on one side of the pole piece, let it stand for 60 minutes, and then visually inspect whether there is any penetration of the penetrant. For samples that cannot be judged visually, observe under a microscope at 20X to see whether there is any penetration of the penetrant on the back of the pole piece; record the degree of penetration (none, slight, moderate, severe); none: no penetration by visual inspection or under a microscope; slight: no penetration by visual inspection, slight penetration by microscope; moderate: point-like penetration by visual inspection; severe: sheet-like penetration by visual inspection.

[0148] (9) Battery performance test:

[0149] (a) 25°C cycle test: In an environment of 25°C, the lithium-ion batteries obtained in the examples and comparative examples were charged at 2C constant current to the full charge voltage (the battery design maximum voltage is 4.5V), then charged at the maximum voltage until the current is 0.02C, and then discharged at a constant current at a discharge current of 0.5C until the final voltage is 3.0V, and the discharge capacity of the first cycle was recorded. The above steps were then repeated to perform charge and discharge cycles, and the capacity retention rate and cell thickness expansion rate when the cycle reached 1000T were recorded.

[0150] (b) Acupuncture test: combined Figure 4 , charge the lithium-ion battery at a current of 1C to the upper voltage limit, and then keep the voltage constant until the current drops to 0.05C and stop charging. Put the fully charged lithium-ion battery into the needle puncture tester, use a steel needle with a diameter of 2mm to pierce the center of the flat area of ​​the lithium-ion battery cell at a rate of 50mm / s, and keep it for 30 minutes. The battery is considered to have passed if it does not catch fire or explode, and 5 batteries are tested in each group.

[0151] (c) Battery long-term storage voltage drop test: 10 pcs of batteries are charged to 50% SOC and placed at 25°C. The initial voltage of the test battery is V0. After N days of standing at room temperature, the voltage of the test battery after N days is Vn. The long-term voltage decay of the battery is V d =(Vn-V0) / (N*24), unit: mV / h, record the long-term voltage decay average of 10pcs batteries.

[0152] Table 1 Parameters of the convex part of the diaphragm and the composite part

[0153]

[0154] Table 2 Mechanical properties of battery core electrode and battery performance parameters

[0155]

[0156]

[0157] In Table 2, the positive electrode sheet is the first electrode sheet, and the negative electrode sheet is the second electrode sheet.

[0158] It is not difficult to see from Table 2 that, in combination with Example 1, Example 2 and Comparative Example 1, after the positive electrode sheet or the negative electrode sheet is compounded with the diaphragm, a convex portion is provided on the positive electrode sheet and / or the negative electrode sheet, the probability of cracks and powder loss in the electrode sheet is significantly reduced, the probability of the diaphragm being pierced by foreign objects is reduced, and the long-term voltage decay of the winding core is reduced, the liquid retention capacity of the battery is increased, and the long cycle performance of the battery is improved.

[0159] Combining Example 3 with Comparative Example 1, it can be seen that by providing a convex portion on the aluminum-plastic film shell, the liquid retention capacity of the battery will be appropriately increased, and the long cycle capacity retention rate of the battery will be increased; by comparing Example 1 with Example 4 and Example 5, it is not difficult to see that as the content of the binder PVDF (Polyvinylidene fluoride) in the positive electrode formula increases, the probability of powder falling off the electrode piece decreases, and the long-term voltage decay of the battery cell decreases.

[0160] In combination with Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that when the binder PVDF content in the positive electrode formula exceeds 2wt%, the toughness of the positive electrode sheet deteriorates, and the electrode sheet is damaged during the embossing process of the composite part; it can be seen from Example 1, Comparative Example 4 and Comparative Example 5 that when the tensile strength of the positive and negative electrode foils is less than 200MPa and 550MPa, respectively, the electrode sheet is damaged due to the inability to withstand excessive pressure during the embossing process, and the smaller the tensile strength of the foil, the more serious the damage to the electrode sheet; it can be seen from Example 1 and Comparative Example 6 that when the binder PVDF content in the positive electrode formula is less than 0.5wt%, the electrode sheet suffers from severe powder loss, resulting in a greater long-term voltage attenuation of the battery cell.

[0161] In the description of the present application, it should be understood that the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0162] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0163] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0164] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0165] The various embodiments or implementation methods in this specification are described in a progressive manner. Each embodiment focuses on the differences from other embodiments, and the same or similar parts between the various embodiments can be referenced to each other.

[0166] It should be noted that the embodiments represented by "one embodiment", "an embodiment", "an exemplary embodiment", "some embodiments", etc. mentioned in the specification may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, such phrases do not necessarily refer to the same embodiment. In addition, when describing specific features, structures or characteristics in conjunction with an embodiment, it is within the knowledge of those skilled in the art to implement such features, structures or characteristics in conjunction with other embodiments that are explicitly or not explicitly described.

[0167] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A winding core, characterized in that: It includes a first pole piece, a diaphragm and a second pole piece; The first pole piece, the diaphragm and the second pole piece are stacked and wound to form the winding core; The diaphragm includes a first diaphragm layer and a second diaphragm layer; the first diaphragm layer is located between the first pole piece and the second pole piece; the first pole piece is located between the first diaphragm layer and the second diaphragm layer; The first diaphragm layer includes a first portion extending beyond the first pole piece, the second diaphragm layer includes a second portion extending beyond the first pole piece, and the first portion and the second portion are adhered; The first diaphragm layer, the first pole piece and the second diaphragm layer form a composite part; the composite part includes a first surface close to the center of the winding core and a second surface away from the center of the winding core; The composite portion is provided with a plurality of convex portions, and the convex portions are bent and protrude from the first surface toward the second surface.

2. The winding core according to claim 1, characterized in that: The composite part further includes recessed portions arranged corresponding to the plurality of protruding portions.

3. The winding core according to claim 1, characterized in that: The first pole piece includes a straight section and an arc section, and the convex portion is arranged on the straight section and / or the arc section.

4. The winding core according to claim 3, characterized in that: The protrusion height of the protrusion of the straight section is greater than the protrusion height of the protrusion of the arc section.

5. The winding core according to claim 3, characterized in that: The straight section of the first pole piece is bonded to the first diaphragm layer and the second diaphragm layer respectively; The arc segment of the first pole piece is not bonded to the first diaphragm layer or the second diaphragm layer.

6. The winding core according to claim 1, characterized in that: The convex portion includes a first convex portion located on the first diaphragm layer, a second convex portion located on the first pole piece, and a third convex portion located on the second diaphragm layer.

7. The winding core according to claim 6, characterized in that: The vertical distance between the vertex of the second convex portion and the first surface is 3-50 microns; and / or, the curvature radius R1 of the second convex portion is 0.5 mm ≤ R1 ≤ 8 mm; And / or, a distance L1 between adjacent second protrusions is 3 mm ≤ L1 ≤ 10 mm.

8. The winding core according to claim 1, characterized in that: The composite part is arranged at intervals along its length direction to form at least two spaced-apart convex areas; the convex area includes a plurality of convex parts.

9. The winding core according to claim 8, characterized in that: The composite part further includes a pole ear area located between the two raised areas, and along the length direction of the first pole piece, the distance from the edge of the pole ear area to the adjacent raised area is 1.5-20 mm; and / or, along the width direction of the first pole piece, the distance from the raised area to the adjacent edge of the composite portion is 0.5-20 mm; And / or, along the length direction of the first pole piece, the distance from the raised area to the adjacent edge of the composite part is 3-50 mm.

10. The winding core according to claim 6, characterized in that: The ratio of the vertical distance between the second protrusion of the first pole piece and the first surface to the thickness of the first pole piece is in a range of 10% to 60%.

11. The winding core according to claim 6, characterized in that: Along the thickness direction of the composite part, the ratio of the center distance between two adjacent second protrusions to the diameter of the second protrusion is in the range of 1.05-3.

12. The winding core according to claim 1, characterized in that: The tensile strength of the diaphragm is greater than or equal to 2500 kgf / cm 2 ; and / or, the puncture strength of the diaphragm is greater than or equal to 260gf.

13. The winding core according to claim 1, characterized in that: The first electrode sheet is a positive electrode sheet, the positive electrode sheet includes a positive electrode collector, and the tensile strength of the positive electrode collector is greater than or equal to 200Mpa; or, the first electrode sheet is a negative electrode sheet, the negative electrode sheet includes a negative electrode collector, and the tensile strength of the negative electrode collector is greater than or equal to 550Mpa.

14. The winding core according to claim 1, characterized in that: The first electrode sheet is a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material layer. In a nitrogen environment, the weight loss rate of the positive electrode active material layer from 35° to a temperature range of 300°C to 600°C is ρ, and ρ satisfies: 1.1% to 6%.

15. The winding core according to claim 14, characterized in that: The positive electrode active material layer comprises a positive electrode active material and a binder, and the binder accounts for 0.5% to 2% of the mass of the positive electrode active material layer.

16. The winding core according to claim 1, characterized in that: The first electrode sheet is a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer comprises a silicon-carbon composite material and / or a silicon-oxygen composite material, and the percentage of silicon element in the negative electrode active layer is 5%-50%; And / or, the particle size Dv50 of the silicon-carbon composite material or the silicon-oxygen composite material is 6 μm-15 μm.

17. The winding core according to claim 1, characterized in that: The absolute plastic deformation rate of the diaphragm is ε1=50%-1600%; and / or the relative plastic deformation rate of the diaphragm is ε2=70%-90%.

18. A battery, characterized in that: It comprises the roll core as described in any one of claims 1 to 17 and a packaging film covering the roll core.

19. The battery according to claim 18, characterized in that The packaging film is provided with a recessed portion, the recessed portion is recessed toward a side away from the winding core body, and the recessed depth of the recessed portion is 10-35 μm.

20. The battery according to claim 19, characterized in that The packaging film comprises a PP layer, an aluminum foil layer and a nylon layer which are stacked, the PP layer is located on a side of the aluminum foil layer close to the winding core, and the PP layer is provided with the recessed portion.

21. The battery according to claim 20, characterized in that The ratio of the depression depth of the depression to the thickness of the aluminum foil layer is less than or equal to 40%; and / or the projection of the depression is circular, and the diameter of the circular embossed portion is 0.8-2 mm.

22. The battery according to claim 19, characterized in that Within a unit area, the ratio of the number of the recessed portions to the area of ​​the side surface of the packaging film is 0.25-0.5:1.

Citation Information

Patent Citations

  • Electrode piece, electrode assembly and battery

    CN117637991A

  • Battery cell and battery

    CN118448749A

  • Coiled electric core and battery

    CN208173683U

  • Electrode assembly, battery monomer, battery and electric equipment

    CN221327759U

  • Negative electrode sheet, lithium-ion battery and electric device

    WO2024077493A1

Cited By

  • Pole piece and diaphragm compounding device, compounding method and compounding unit

    CN121790692A